PERAN TERJEMAH DALAM KEBUDAYAAN DAN PERSOALAN IDENTITAS - Khairon Nahdiyyin (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
This paper aims at elaborating the relationship of translation, culture, and identity. Translation is one means of cultural development. It adopts not only from other elements, but also from other culture to be dialogued and equivalented with the target culture. Within this